2015
DOI: 10.1186/s13063-015-0858-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrating smoking cessation and alcohol use treatment in homeless populations: study protocol for a randomized controlled trial

Abstract: BackgroundDespite progress in reducing cigarette smoking in the general U.S. population, smoking rates, cancer morbidity and related heart disease remain strikingly high among the poor and underserved. Homeless individuals’ cigarette smoking rate remains an alarming 70 % or greater, and this population is generally untreated with smoking cessation interventions. Furthermore, the majority of homeless smokers also abuse alcohol and other drugs, which makes quitting more difficult and magnifies the health consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The homeless population struggles with several treatment engagement issues for smoking cessation, including lack of treatment resources integrating both SUD and smoking cessation treatment and an absence of smoking cessation treatment in most organizations serving the homeless. 41,13 The present study suggests that small and relatively simple tobacco-specific modifications can be easily layered onto existing substance use disorder treatments to enhance engagement in tobacco cessation among homeless Veterans seeking SUD treatment . …”
Section: Discussionmentioning
confidence: 82%
“…The homeless population struggles with several treatment engagement issues for smoking cessation, including lack of treatment resources integrating both SUD and smoking cessation treatment and an absence of smoking cessation treatment in most organizations serving the homeless. 41,13 The present study suggests that small and relatively simple tobacco-specific modifications can be easily layered onto existing substance use disorder treatments to enhance engagement in tobacco cessation among homeless Veterans seeking SUD treatment . …”
Section: Discussionmentioning
confidence: 82%
“…Studies have shown that engaging in smoking cessation does not adversely affect substance use behaviors (Apollonio 2016), and has in-creased the number of days abstinent from alcohol . More recent research efforts such as have focused on designing interventions to reduce smoking initiation among youth experiencing homelessness (Shadel 2014), and to improve quit rates among adults experiencing homelessness (Baggett 2017;Carpenter 2015;Ojo-Fati 2015;Okuyemia 2006b;Okuyemi 2013;Rash 2018).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…PTQII included (1) a higher dose of pharmacotherapy (nicotine patch combined with nicotine gum or lozenge) and a longer duration of prescribed use (i.e., 12 versus 8 weeks), (2) an increased number of counseling sessions (12 versus 8 sessions over 3 months), (3) an increase in the duration of individual sessions from 15 to 30 min to 45 to 60 min, (4) counseling sessions utilizing cognitive behavioral therapy (CBT) strategies to enable counselors to provide more strategies during counseling sessions, and (5) counseling content targeting alcohol abstinence in addition to smoking cessation. Details regarding the design of this study have been published [ 26 ]. Briefly, the study utilizes a three-group design that includes (1) Usual care (UC) for smoking and alcohol cessation, (2) Intensive smoking cessation plus UC alcohol abstinence counseling (IS), and (3) Integrated Intensive Smoking and Intensive Alcohol Counseling (IntS + A).…”
Section: Introductionmentioning
confidence: 99%
“…Research staff in both studies received traditional research training that included protecting sensitive information regarding drug and alcohol use, adequate Health Insurance Portability and Accountability Act of 1996 (HIPAA) and Collaborative Institutional Training Initiative (CITI) research training, sexual harassment prevention training, protection of participants reporting sexual harassment and administering unbiased questionnaires [ 25 , 26 ]. It was important to train staff in a variety of additional day-to-day challenges that this population frequently encounters and their relationship to professional boundaries.…”
Section: Introductionmentioning
confidence: 99%